Immunohistochemistry Staining-Proven Cytomegalovirus Colitis in Living Donor Liver Transplantation - Shu-Hsien Lin; Kun-Ta Wu; Chih-Chi Wang; Ting-Ting Liu; Hock-Liew Eng; King-Wah Chiu (Viruses, 2022)
Background and Aims: Cytomegalovirus (CMV) infection is a common occurrence in liver transplantation (LT) even in an era of preventive strategies. However, the diagnosis of CMV colitis remains challenging. This study aimed to focus on the clinical significance of endoscopic biopsy-proven CMV colitis in patients following living donor liver transplantation (LDLT). Methods: From January 2007 to December 2021, a total of 55 CMV colitis cases were retrospectively enrolled and divided into a non-LDLT group in 53 and an LDLT group in 2 cases. Clinical demographics, diagnostic measurement, histopathology, and anti-viral therapy were investigated. Results: There were 1630 cases undergoing LDLT in the period 2007–2021, with only 2 recipients being confirmed to have CMV colitis in 2021 (2/114, 1-year incidence: 1.75%). Comparisons between the 53 non-LDLT cases and 2 LDLT cases are as follows: Serum anti-CMV immunoglobulin M (IgM) was shown to be positive (n = 3, 5.5% vs. n = 0, p = 1.0) and negative (n = 20, 37.7% vs. n = 2, 100%, p = 0.16); anti-CMV immunoglobulin G (IgG) was positive (n = 19, 35.8% vs. n = 2, 100%, p = 0.14) and none were negative; CMV DNAemia was shown to be detectable (n = 14, 26.4% vs. n = 1, 50%, p = 0.47) and undetectable (n = 14, 26.4% vs. n = 1, 50%, p = 0.47). Among the two recipients with CMV colitis, one had CMV DNAemia and the other had no CMV DNAemia upon the development of symptoms; negative anti-CMV-IgM and positive anti-CMV-IgG were observed both pre-transplant and post-transplant; finally, CMV colitis was documented based on the presence of inclusion bodies and positive immunohistochemistry (IHC) staining in histology. Conclusion: Patients with immunocompromised status, in particular organ transplantation, may have positive serum anti-CMV IgM/IgG antibodies both before and after transplantation. This study emphasized the fact that endoscopic biopsy with IHC staining may be a more powerful tool for making an accurate diagnosis of CMV colitis in the setting of living donor liver transplantation.